In Vitro Infectivity of Leishmania major Isolated from Patients with Different Clinical Forms of Cutaneous Leishmaniasis and Its Association with Parasite Zymodems - GR Hatam; H Rezanezhad; MH Motazedian; B Sarkari (Iranian Journal of Parasitology, 2009)
Background: The aim of this study was to characterize the Leishmania parasites isolated from cutaneous leishmaniasis (CL) patients in Fars Province in Iran and to compare the potential infectivity of the isolates in macrophage cell line. Moreover, attempt was made to find out the association between parasite infectivity and their zymodems.